The Pengaruh Inflasi, Suku Bunga, dan Nilai Tukar terhadap Harga Saham Perbankan di BEI Periode 2020-2024 - Fadila, Ririn Nur; Susilo, Dwi Ermayanti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This research seeks to examine the impact of inflation, interest rates, and exchange rates on the stock prices of banking firms listed on the Indonesia Stock Exchange for the period from 2020 to 2024. The primary concern addressed is the inconsistency found in previous empirical studies regarding the effect of macroeconomic variables on banking stock prices, especially in the post-pandemic era marked by significant global economic fluctuations. This study employs a quantitative methodology utilizing secondary data sourced from the Indonesia Stock Exchange, Bank Indonesia, and the Central Bureau of Statistics. The sample comprises 27 banking companies chosen through purposive sampling, yielding a total of 135 observations. The data were analyzed using multiple linear regression after confirming that all classical assumption tests were met. The findings reveal that inflation exerts a positive and significant influence on stock prices, with a coefficient of 0.700 (p < 0.001). Conversely, interest rates have a negative and significant impact, reflected by a coefficient of −0.499 (p < 0.001). Exchange rates also demonstrate a positive and significant effect, with a coefficient of 0.577 (p < 0.001). The coefficient of determination (R²) of 64.5% suggests that these three variables account for the majority of the variation in banking stock prices, while the remaining 35.5% is attributed to other factors not included in the model. The originality of this study is highlighted by its focus on a recent observation period that captures adjustments in global monetary policy. This research provides valuable insights for investors, regulators, and banking management in comprehending the macroeconomic factors that influence banking stock prices.